Successful Pregnancy after Simultaneous Pancreas-Kidney Transplantation. (10th July 2011) - Smyth, A.; Gaffney, G.; Hickey, D.; Lappin, D.; Reddan, D.; Dunne, F.
Abstract : The effect of pregnancy on simultaneous pancreas-kidney transplant recipients has previously been described, but experience is limited. We describe the case of a thirty-five-year-old female who previously underwent simultaneous pancreas-kidney transplant for type 1 diabetes mellitus-complicated nephropathy. An integrated multidisciplinary team including the transplant team, nephrologist, endocrinologist, and obstetrician closely followed progress during pregnancy. Blood glucose levels and HbA1c remained within normal limits, and she did not require insulin treatment at any point. She experienced deterioration in renal indices and underwent an uncomplicated, elective Caesarean section at thirty-week gestation. She delivered a male infant of 1.18 kg, appropriate for gestational age, who had hypothermia and respiratory distress, which required intubation and ventilation and an eleven-week stay in the special care baby unit. At eighteen-month followup the infant shows normal development, and there has been no deterioration in either grafts' function.